Highly Fluorinated Peptide Probes with Enhanced In Vivo Stability for 19F‐MRI. Issue 41 (8th September 2022) - Meng, Beibei; Grage, Stephan L.; Babii, Oleg; Takamiya, Masanari; MacKinnon, Neil; Schober, Tim; Hutskalov, Illia; Nassar, Omar; Afonin, Sergii; Koniev, Serhii; Komarov, Igor V.; Korvink, Jan G.; et al.
Abstract: A labeling strategy for in vivo 19 F‐MRI (magnetic resonance imaging) based on highly fluorinated, short hydrophilic peptide probes, is developed. As dual‐purpose probes, they are functionalized further by a fluorophore and an alkyne moiety for bioconjugation. High fluorination is achieved by three perfluoro‐ tert ‐butyl groups, introduced into asparagine analogues by chemically stable amide bond linkages. d ‐amino acids and β‐alanine in the sequences endow the peptide probes with low cytotoxicity and high serum stability. This design also yielded unstructured peptides, rendering all 27 19 F substitutions chemically equivalent, giving rise to a single 19 F‐NMR resonance with <10 Hz linewidth. The resulting performance in 19 F‐MRI is demonstrated for six different peptide probes. Using fluorescence microscopy, these probes are found to exhibit high stability and long circulation times in living zebrafish embryos. Furthermore, the probes can be conjugated to bovine serum albumin with only amoderate increase in 19 F‐NMR linewidth to ≈30 Hz. Overall, these peptide probes are hence suitable for in vivo 19 F‐MRI applications. Abstract : Hydrophilic short peptide probes for 19 F‐MRI carrying up to 27 environmentally equivalent 19 F atoms, by repeated incorporation of perfluoro‐ tert ‐butyl‐derivatized asparagine residues, are synthesized. These peptide probes exhibit low cytotoxicity and high serostability due to d ‐amino acids, and retain sensitive 19 F signals even after conjugation to albumin or glutathione. Dual‐purpose fluorescently labeled peptide probes show long circulation time in zebrafish embryos.